Evaluation of Current Households Management Practices of Solid Wastes from Pharmaceuticals in Soc Trang city, Vietnam - T. T. Tien; N. T. Giao (Journal of Applied Sciences and Environmental Management)
Pharmaceutical wastes could pose serious health and environmental risk if inappropriately managed within the household. Hence, the objective of this paper was to evaluate the current households’ management practices of solid wastes from pharmaceuticals in Soc Trang city, Vietnam using semi-structured questionnaires. The results showed that more than 300 different pharmaceutical brand names belonging to 14 groups of pharmaceutical drugs have been used in which digestive, pain relievers, antipyretics, steroid anti-inflammatory drugs, gout, bone and joint diseases, cardiovascular, parasitic, anti-inflammatory, antiviral, and antifungal drugs were the commons. Thirty-seven actively harmful ingredients to the environment and organisms were identified in the study area. The management of pharmaceutical wastes has not been well practiced since the unused medicines and its packaging were discarded with domestic solid wastes, burying, burning and flushing into the toilet. The interviewees reported that the reasons they discharged medicines are health improvement, experiencing side effects or failure in the treatment process. The interviewees did not have much knowledge of the impact of potentially harmful chemicals containing in the discarded medicines on health and ecosystems. This could lead to increasingly released and accumulating pharmaceutical wastes in environments. Appropriate collection and awareness raising for local people in the management of pharmaceutical wastes in the study area are essential.